ELETRODO MODIFICADO COM FILMES DE QUITOSANA-NiTsPc PARA QUANTIFICAÇÃO DE ÁCIDO LIPÓICO EM SUPLEMENTO DIETÉTICO - Santos, Ana Caroline Ferreira (2013)
This work describes the development of electroanalytical procedures for alpha-lipoic acid (ALA) determination in dietary supplement using a glassy carbon (GC) electrode modified with chitosan (CT) and nickel tetrasulfonated phthalocyanine (NiTsPc) films. The linear sweep voltammograms of ALA oxidation on the GC/CTNiTsPc electrode presented an irreversible peak near 0,85 V vs Ag/AgCl, a value about 100 mV less positive than those recorded on the unmodified GC and GC/CT electrodes. In addition, the modification resulted in a pronounced increase in the peak current value. Ultraviolet-visible spectroscopic characterization of the CTNiTsPc film showed a shift in the Q band of the NiTsPc, when compared to the spectrum recorded in a 1,0x10 mol Lˉ¹ NiTsPc aqueous solution, and indicated a possible interaction of the sulfonic groups with the positively charged amine groups in the CT film. From cyclic voltammetry (CV), differential pulse voltammetry (DPV) and square wave voltammetry (SWV) data, analytical curves were constructed and showed good linearity and sensitivity for the dependence between the oxidation peak current and the ALA concentration in solution. The CV technique showed the Best detection (9,72x10ˉ⁸ mol Lˉ¹) and quantification (3,24x10-7 mol Lˉ¹) limit values for ALA in solution. Determination of ALA in dietary supplement using the GC/CT-NiTsPc electrode showed results in accordance with the obtained using a chromatographic method at a 95% confidence level.